2020
DOI: 10.1002/bjs5.50250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraperitoneal chemotherapy concentration on morbidity and survival

Abstract: Background Selected patients with colorectal peritoneal metastases are treated with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). The concentration of intraperitoneal chemotherapy reflects the administered dose and perfusate volume. The aim of this study was to calculate intraperitoneal chemotherapy concentration during HIPEC and see whether this was related to clinical outcomes. Methods An observational multicentre study included consecutive patients with colorectal perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Concentration-based protocols use a perfusate with a fixed chemotherapy concentration, leading to more predictable concentrations at the peritoneal surface, but possibly more variation in systemic exposure. One multicenter study 11 reported that variation in chemotherapy concentrations of the HIPEC perfusate did not affect postoperative complications or survival rates.…”
Section: Dosing and Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration-based protocols use a perfusate with a fixed chemotherapy concentration, leading to more predictable concentrations at the peritoneal surface, but possibly more variation in systemic exposure. One multicenter study 11 reported that variation in chemotherapy concentrations of the HIPEC perfusate did not affect postoperative complications or survival rates.…”
Section: Dosing and Durationmentioning
confidence: 99%
“…Approximately 25% of patients in the trial had a peritoneal cancer index of greater than 15, which has previously been reported as the threshold beyond which CRS-HIPEC is not beneficial. 60,76 In addition, subgroup analyses of the PRODIGE 7 data suggest a survival benefit of HIPEC in patients with intermediate extent of peritoneal metastases (peritoneal cancer index, [11][12][13][14][15].…”
Section: Current Role Of Hipec In the Treatment Of Colorectal Cancer ...mentioning
confidence: 99%
“…In four observational studies, the high-dose OX regimen was compared with high-dose MMC, with no difference in survival but more severe complications in OX-treated patients. 26 , 29 , 30 , 34 …”
Section: Resultsmentioning
confidence: 99%
“…The concentrations were 0.045%, 0.06%, 0.09%, 0.135% and 0.18%, respectively. Oxaliplatin (Medoxa, medac GmbH, Wedel, Germany) was diluted in 5% glucose solution [ 27 , 28 ]. The concentration in each well was 0.24 mg/ml (= 0,6 mmol/L) which corresponds to common HIPEC application amounts of 960 mg/4 L (480 mg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%